2005
DOI: 10.1002/bio.819
|View full text |Cite
|
Sign up to set email alerts
|

Time‐resolved spectroscopic fluorescence imaging, transient absorption and vibrational spectroscopy of intact and photo‐inhibited photosynthetic tissue

Abstract: Fluorescence, absorption and vibrational spectroscopic techniques were used to study spinach at the photosystem II (PS II), chloroplast and cellular levels and to determine the effects and mechanisms of ultraviolet-B (UV-B) photoinhibition of these structures. Two-photon fluorescence spectroscopic imaging of intact chloroplasts shows significant spatial variations in the component fluorescence spectra in the range 640-740 nm, indicating that the type and distribution of chlorophylls vary markedly with position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…A 33-kDa protein of water-splitting complex is sensitive to UV-B (Prabha and Kulandaivelu 2002); thus, its degradation contributes importantly to the decline of electron transport rate. By transient absorption measurements and vibrational spectroscopic techniques, Lukins et al (2005) had shown that the predominant sites of UV-B damage in PS II were at the oxygen-evolving center (OEC) itself, as well as at specific locations near the OEC-binding sites. In higher plant such as spinach, UV-B sensitivity has been reported to be dependent on the oxidation state of the water-splitting complex of PS II (Szilárd et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A 33-kDa protein of water-splitting complex is sensitive to UV-B (Prabha and Kulandaivelu 2002); thus, its degradation contributes importantly to the decline of electron transport rate. By transient absorption measurements and vibrational spectroscopic techniques, Lukins et al (2005) had shown that the predominant sites of UV-B damage in PS II were at the oxygen-evolving center (OEC) itself, as well as at specific locations near the OEC-binding sites. In higher plant such as spinach, UV-B sensitivity has been reported to be dependent on the oxidation state of the water-splitting complex of PS II (Szilárd et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Only few examples of fluorescence lifetime imaging of plants have been reported in literature. These include the assessment of environmental stress, such as the effect of herbicides260 and plant adaptation to excessive light 261…”
Section: Autofluorescencementioning
confidence: 99%
“…This can be correlated to the responses of the photosynthetic apparatus to environmental effects (Holub et al 2000;Lukins et al 2005). Two-photon excitation FLIM has been used to study photosynthesis in plant leaves, with the goal of monitoring chloroplast responses to changes in environmental conditions, and it has been found that FLIM measurements might detect variations in plastidic granum density (Broess et al 2009).…”
Section: Introductionmentioning
confidence: 99%